Dividends and Corporate Shareholders - Barclay, Michael J.; Holderness, Clifford G.; Sheehan, Dennis P. (Review of Financial Studies, 2009)
Corporations uniquely have a tax preference for cash dividends. Nevertheless, dividends do not increase following trades of large-percentage blocks of stock from individuals to corporations. Moreover, although one-third of firms have corporate blockholders, 68% of these firms pay no dividends, and ownership is not clustered at levels that increase the tax benefits of dividends. These findings are not driven by the investing firms' tax rates or by agency problems. Instead, operating companies expand the target firms and pursue joint ventures. Dividends are lower with these investors. Financial investors are not attracted to dividend-paying firms and tend to be passive. The Author 2008. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org., Oxford University Press.